Correlation of Teacher Creativity in Teaching with Student's Learning Achievement - Belsasar Sihombing; Osco Parmonangan Sijabat (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: This study aimed to determine the correlation between teacher creativity in teaching and learning achievement. Methodology: This study uses quantitative research methods with a correlational research design. The population in this study was class V elementary school 091299 Sipoldas. The sample in this study amounted to 30. This study used a saturated sample because the population of class V students at elementary school 091299 Sipoldas were all sampled. The data collection techniques used questionnaires and documentation. The data analysis technique used is a prerequisite test and hypothesis testing. Main Findings: Based on the results of this study, it was concluded that there was a significant correlation between teacher creativity in teaching and learning achievement of fifth-grade students at elementary school 091299 Sipoldas because the value of rcount > rtable (0.552 > 0.361) and the significance value of tcount > ttable (3.505 > 1.701) so that it can be concluded that Ha is accepted and H0 is rejected. Novelty/Originality of this study: Teachers who don't pay attention to students in the class will impact student learning achievement, which is getting lower and educational goals in schools are not achieved. Therefore, teacher creativity is needed in assembling a lesson to produce student learning achievement.